2016
DOI: 10.1021/acs.analchem.6b00422
|View full text |Cite
|
Sign up to set email alerts
|

Dual Site-Controlled and Lysosome-Targeted Intramolecular Charge Transfer–Photoinduced Electron Transfer–Fluorescence Resonance Energy Transfer Fluorescent Probe for Monitoring pH Changes in Living Cells

Abstract: Acidic pH is a critical physiological factor for controlling the activities and functions of lysosome. Herein, we report a novel dual site-controlled and lysosome-targeted intramolecular charge transfer-photoinduced electron transfer-Fluorescence resonance energy transfer (ICT-PET-FRET) fluorescent probe (CN-pH), which was essentially the combination of a turn-on pH probe (CN-1) and a turn-off pH probe (CN-2) by a nonconjugated linker. Coumarin and naphthalimide fluorophores were selected as donor and acceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(91 citation statements)
references
References 51 publications
2
89
0
Order By: Relevance
“…For a FRET system, a substantial spectral overlap which is necessary between the donor emission band and the acceptor absorption band is closely related to the energy transfer efficiency. The naphthalimide derivatives have broad absorption spectra (450-650 nm) [31][32][33], which covers a part of absorption of rhodamine (500-560 nm) and fulfills a favorable condition for FRET (Fig. S1).…”
Section: Scheme 1 Three Kinds Of Rhodamine-based Fret Probementioning
confidence: 99%
“…For a FRET system, a substantial spectral overlap which is necessary between the donor emission band and the acceptor absorption band is closely related to the energy transfer efficiency. The naphthalimide derivatives have broad absorption spectra (450-650 nm) [31][32][33], which covers a part of absorption of rhodamine (500-560 nm) and fulfills a favorable condition for FRET (Fig. S1).…”
Section: Scheme 1 Three Kinds Of Rhodamine-based Fret Probementioning
confidence: 99%
“…By further attaching a morpholine containing moiety as a lysosome targeting group, [10] Lyso-SOP-green was obtained. Fluorescence studies showed that the superoxide selectivity of Lyso-SOP-green are very similar to those of SOP-green, demonstrating that this bond cleavage-based strategy could be versatilely applied to other superoxide-triggered release.…”
Section: Resultsmentioning
confidence: 99%
“…Optical detection methods are attracting increasing research interest owing to their high sensitivity, short response time, non-invasive nature, capacity for real-time monitoring and easy sample preparation. [30][31][32][33] Based on the good nucleophilic and reducing chemistry of H 2 S, researchers have been developing optical probes with high sensitivity, selectivity and biocompatibility for the detection of H 2 S in biological systems. These probes are based primarily on specic H 2 S-induced reactions, including azide reduction, [34][35][36] nitro reduction, 37,38 removal of quenchers (such as copper(II)), [39][40][41] and nucleophilic reactions, [42][43][44] to allow uorescence to be turned on for H 2 S detection at different biological levels.…”
Section: Introductionmentioning
confidence: 99%